Work Index and Contextual Variables as Predictors of Emergency Nurses’ Career Success - Mohammadzadeh, Ali; Asghari, Elnaz; Ghafourifard, Mansour (Nurse Media Journal of Nursing, 2021)
Background: The stressful work environment of emergency departments needs competent nurses to be successful in their careers. Although the work environment significantly affects nurses’ quality of care and job satisfaction, studies on the relationship between the work environment and career success are still limited. Therefore, it is imperative to investigate how individual and environmental factors predict the career success of nurses in the emergency department.Purpose: This study was conducted to identify the predictors of career success of emergency nurses based on work index and contextual variables.Methods: This cross-sectional study was conducted in eight university hospitals in Tabriz, Iran. The career success scale and the Nursing Work Index (PES-NWI) were completed by 193 emergency nurses selected using a stratified random sampling technique. Data were analyzed using a multivariate regression analysis.Results: The mean and standard deviation of nurses’ scores were 168.59±15.54 for the career success scale (range: 39-195) and 2.64±0.48 for the PES-NWI (range: 1-4). According to multiple linear regression analysis, nursing work index and hospital type were significant predictors of nurses’ career success (R2=0.17, adjusted R2=0.11, p<.01).Conclusion: Nursing work index and hospital type were significant predictors of nurses’ career success. Nursing managers and leaders should provide healthy work environments to help nurses increase their career success.